STRATEGI PEMBELAJARAN INKUIRI DALAM MENGATASI KESULITAN BELAJAR SISWA DI MADRASAH - Moh Fachri; Farida Nur Azizah (MANAGERE : Indonesian Journal of Educational Management, 2020)
This study aims to understand the inquiry learning strategy in overcoming the learning difficulties of class IX students at MTs Mabadius Shaleh, Mlandingan, Situbondo. Application of Inquiry provides an alternative solution for teachers in creating interesting and fun learning environments. This research uses a qualitative approach to the type of case study. The technique of collecting data is done through interviews, observation and documentation. The results showed that the application of the inquiry method at Mabadius Shaleh MTs, Mlandingan Situbondo had a very big impact in overcoming child learning difficulties. Students who are initially less active and have difficulty understanding the material, they are able to understand the material taught by the teacher well through inquiry learning. This is indicated by an increase in motivation and student achievement in class IX.